Princess de Talmont and the Voltaire Connection. - Dzwigala, Wanda (Polish Review, 2025)
Princess de Talmont (née Maria Anna Ludwika Jabłonowska) arrived in France from her native Poland in the early decades of the eighteenth century. Her family ties to the Versailles and Lunéville courts (as first cousin of the exiled Polish monarch, Stanisław Leszczyński) brought her widespread notoriety in French society. Not only was she a dedicated supporter of Leszczyński's bid for the Polish throne, the Polish princess supported other political causes throughout her life, inter alia, she advocated on behalf of Poland's political independence from foreign intervention in the closing decades of the eighteenth century. Furthermore, Princess de Talmont was a patron of the French Enlightenment—she frequented Parisian intellectual salons, corresponded and associated with the philosophes and encyclopédistes, as well as prominent artists and writers, and espoused many of the progressive views of Enlightenment thought. For example, the Polish princess sympathized with the theory of deism which was popular among Enlightenment thinkers, and supported the education of women, particularly women of the aristocracy. In 1738, she established a personal acquaintance with Voltaire, which spanned over thirty-five years and was based on mutual respect and admiration, yet distinguished by opposing political views. The purpose of this article is to assess the relationship between Princess de Talmont and Voltaire, and determine the extent to which the Polish princess was able to influence Voltaire's views of Poland, with specific reference to the Confederates of Bar and the political turmoil in Poland on the eve of the First Partition.